Conexiones culturales y patrimonio prehistórico - Garrido Anguita, Juan Manuel; Martín de la Cruz, José C. (Archaeopress Archaeology, 2023)
Paying homage to José C. Martín de la Cruz, this volume considers Bronze Age intercultural connections in the Mediterranean area, investigates the first settlements and early food producing societies, examines our remote past and its natural environment, and closes with multidisciplinary prehistoric studies from a range of scientific fields.